TIN Generation from Digitized Contour Lines - Abdul Rahman, Alias; Piloux, Marakot (Fakulti Ukur dan Harta Tanah, 1993)
This paper desribes one of the possibilities of generating TIN from digitized contour lines. A concept of Borgefors distance transform is utilised to construct thiessen polygons. The topology of the centroid point of the polygons, the neighbouring points is established. The connection of these points eventually formed a series of irregular triangles(i.e. TIN).